(untitled) (Journal of the Bangladesh Agricultural University, 2019)
This research was aimed to develop functional drink based on foam-mat drying of papaya. Papaya pulp was foamed by the addition of 10, 15 and 20% egg white (w/w). Foamed papaya slurry was dried by using hot air at 60 0C for 5 hours. Drying yield and protein content of dried powder increased with the increase of egg white. Vitamin C decreased in powder due to heat degradation. Higher foam thickness resulted in longer drying time. Drying time of foamed pulp was much lower than the non-foamed pulp. Moisture content, reconstitution and water holding capacity of foam-mat dried powder were in the range of 3.27-3.93%, 82.43-83.53% and 5.23-5.93 g/g, respectively. Functional drinks were formulated by dry blending of foam-mat dried papaya powder and other ingredients at the ratio of 6:4, 5:5 and 4:6 (w/w) of foam-mat dried papaya powder and skim milk. Different ratio of foam-mat dried papaya and skim milk powder affected the physicochemical properties (moisture content, reconstitution rate, and water holding capacity) and sensory properties (color, viscosity, flavor and taste) of the product. The reconstituted drink at a ratio of 4:6 of foam-mat dried papaya powder and skim milk retained the best sensory properties. J Bangladesh Agril Univ 17(3): 388–395, 2019